Question
upstudy study bank question image url

\[ \begin{array}{l} =2^{6} \cdot 3^{1} \\ =192 \end{array} \] \[ \begin{array}{l} =\frac{2^{x}(3)}{3.2^{x}} \\ =1 \end{array} \] EXERCISE 1 Simplify the expressions without using a calculator: (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) \( 2 \frac{2\left(2 a^{4}\right)^{3}}{16 a^{12}} \) (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) \( 4 \quad \frac{3 a^{3} \times 5 a^{5}}{\left(5 a^{3}\right)^{2}} \) \( 5 p^{x-1} p^{x+1} \) (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) \( 7 \quad 16^{4 x} \div 4^{2 x} \) (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) 9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) \( 10 \frac{3^{x}+3^{x+1}}{8} \) Negative exponents and the meaning of \( a^{0} \) \( a^{0}=1 \) because \( 5 \div 5=1 \) and \( 5^{1} \div 5^{1}=\frac{5^{1}}{5^{1}}=5^{1-1}=5^{0}=1 \quad \) Using Law 2 For example: \( (2 x)^{0}=1 ; 2 x^{0}=2 \times 1=2 ;(a+b)^{0}=1 \)

Ask by Klein Mccarthy. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the simplified expressions: 1. \( \frac{4}{5} a^{8} b^{14} \) 2. \( 2 \) 3. \( 3 a^{2} \) 4. \( \frac{3}{5} a^{2} \) 5. \( p^{2x} \) 6. \( -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \) 7. \( 4^{6x} \) 8. \( 8 \cdot 3^{4x - 5} \) 9. \( 2^{1010} \cdot 5^{1011} \) 10. \( \frac{3^{x}}{2} \)

Solution

Let's simplify each expression step by step. ### (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) 1. Multiply the coefficients: \[ \frac{1}{4} \times \frac{16}{5} = \frac{16}{20} = \frac{4}{5} \] 2. Combine the powers of \( a \): \[ a^{5} \times a^{3} = a^{5+3} = a^{8} \] 3. Combine the powers of \( b \): \[ b^{12} \times b^{2} = b^{12+2} = b^{14} \] 4. Final result: \[ \frac{4}{5} a^{8} b^{14} \] ### (2) \( 2 \frac{2(2 a^{4})^{3}}{16 a^{12}} \) 1. Simplify \( (2 a^{4})^{3} \): \[ (2 a^{4})^{3} = 2^{3} a^{12} = 8 a^{12} \] 2. Substitute back into the expression: \[ 2 \frac{2 \cdot 8 a^{12}}{16 a^{12}} = 2 \frac{16 a^{12}}{16 a^{12}} = 2 \cdot 1 = 2 \] ### (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) 1. Combine like terms in the numerator: \[ 6 a^{4} + 9 a^{4} = 15 a^{4} \] 2. Simplify the fraction: \[ \frac{15 a^{4}}{5 a^{2}} = 3 a^{4-2} = 3 a^{2} \] ### (4) \( \frac{3 a^{3} \times 5 a^{5}}{(5 a^{3})^{2}} \) 1. Simplify the numerator: \[ 3 a^{3} \times 5 a^{5} = 15 a^{3+5} = 15 a^{8} \] 2. Simplify the denominator: \[ (5 a^{3})^{2} = 25 a^{6} \] 3. Combine: \[ \frac{15 a^{8}}{25 a^{6}} = \frac{15}{25} a^{8-6} = \frac{3}{5} a^{2} \] ### (5) \( p^{x-1} p^{x+1} \) 1. Combine the powers: \[ p^{(x-1) + (x+1)} = p^{2x} \] ### (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) 1. Expand the square: \[ (-4 a^{2}+b^{3})^{2} = 16 a^{4} - 8 a^{2} b^{3} + b^{6} \] 2. Multiply by \(-2\): \[ -2(16 a^{4} - 8 a^{2} b^{3} + b^{6}) = -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \] ### (7) \( 16^{4 x} \div 4^{2 x} \) 1. Rewrite in terms of base \( 4 \): \[ 16 = 4^{2} \Rightarrow 16^{4x} = (4^{2})^{4x} = 4^{8x} \] 2. Now simplify: \[ \frac{4^{8x}}{4^{2x}} = 4^{8x - 2x} = 4^{6x} \] ### (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) 1. Rewrite in terms of prime factors: \[ 12 = 2^{2} \cdot 3^{1}, \quad 27 = 3^{3}, \quad 18 = 2^{1} \cdot 3^{2} \] 2. Substitute: \[ \frac{(2^{2} \cdot 3^{1})^{x+1} \cdot (3^{3})^{x-2}}{(2^{1} \cdot 3^{2})^{2x-1}} = \frac{2^{2(x+1)} \cdot 3^{x+1 + 3(x-2)}}{2^{2x-1} \cdot 3^{2(2x-1)}} \] 3. Simplify: \[ = \frac{2^{2x+2} \cdot 3^{x+1 + 3x - 6}}{2^{2x-1} \cdot 3^{4x-2}} = \frac{2^{2x+2 - (2x-1)} \cdot 3^{4x - 5}}{1} = 2^{3} \cdot 3^{4x - 5} = 8 \cdot 3^{4x - 5} \] ### (9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) 1. Rewrite \( 10^{1000} \): \[ 10^{1000} = (2 \cdot 5)^{1000} = 2^{1000} \cdot 5^{1000} \] 2. Substitute: \[ \frac{2^{2010} \cdot 5^{2011}}{2^{1000} \cdot 5^{1000}} = 2^{2010 - 1000} \cdot 5^{2011 - 1000} = 2^{1010} \cdot 5^{1011} \] ### (10) \( \frac{3^{x}+3^{x+1}}{8} \) 1. Factor out \( 3^{x} \): \[ = \frac{3^{x}(1 + 3)}{8} = \frac{3^{x} \cdot 4}{8} = \frac{3^{x}}{2} \] ### Summary of

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

If you're curious about how our understanding of exponents has evolved, you'll be fascinated to know that ancient civilizations like the Babylonians had a rudimentary grasp of higher powers and their relationships, laying foundational work that centuries later was formalized by mathematicians such as Blaise Pascal and Leonhard Euler. These greatest minds turned exponential growth into a cornerstone of modern algebra, affecting everything from physics to finance! When tackling those exponent problems, a common pitfall is mismanaging negative and zero exponents—don't forget, situations like \( a^0 \) simplistically mean "one," and \( a^{-n} \) flips into \( \frac{1}{a^n} \). So, channel your inner mathematician: always keep those laws of exponents handy and simplify carefully, ensuring you're following each step without skipping! Happy calculating!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy